The Evolution of Russian Military Thought: Integrating Hybrid, New-Generation, and New-Type Thinking. Issue 4 (1st October 2016) - Thomas, Timothy
ABSTRACT: This article highlights both the evolution of Russian thinking and Russian General Staff interest in a concept known as new-type warfare. In early 2015, General-Lieutenant A. V. Kartapolov, then director of the Russian General Staff's Main Operation's Directorate, both explained the concept in an article written for the Journal of the Academy of Military Science and provided a schematic visualization of the concept. Before this revelation, Western analysts had thought that the Russian military was using either hybrid warfare concepts or new-generation warfare (NGW) means. In response to these assertions from the West, Russian military officers stated that they do not conduct hybrid war, noting clearly that this is a Western method for waging modern war. However, two retired Russian officers did write extensively on NGW in 2012 and 2013, which prompted much discussion in the West. This concept was not directly refuted by Russian military officers, which may mean it is still a relevant way to consider warfare within the ranks of military professionals. At this moment, however, with General Staff backing, it appears that the new-type warfare concept has won out over NGW, although an evolution and integration of thinking is also apparent in the progression from hybrid, to NGW, to new-type warfare.